OPTIMASI PRODUKSI HORMON, NITROGEN TOTAL DAN KEPADATAN SEL AZOTOBACTER PADA INOKULAN CAIR MELALUI PENAMBAHAN Fe DAN Mo - Danapriatna, Nana; Hutagalung, Benny; Hindersah, Reginawati (Jurnal Agroteknos, 2013)
Production of liquid biofertilizer Azotobacter requires pure inoculum with N2 fixation capacity, hormone production, and optimal cell density.   This research was conducted to determine the effect of Fe-Mo microelement and Azotobacter inoculant concentration   on enhancement of hormones and total nitrogen content as well as  Azotobacter population in liquid culture. The experiment used Randomized Completely Design with six treatments and three replications. The treatments were combination of inoculant concentration (without, 5%, 10% and 15%) and  Fe-Mo solution (with and without Fe-Mo).  The result showed that addition of Fe and Mo microelements in liquid culture increased Cytokinin production as well as population density of Azotobacter.  Inoculant concentration of 10% with the addition of micronutrients  Fe  and  Mo  was  able  to  optimize  the  production  of hormones, nitrogen fixation, and cell density of Azotobacter. Keywords : Fe, Mo, Total Nitrogen, Hormone, Azotobacter